Kajian Social Game Pet Society terhadap Pengaruh Gaya Hidup User Ditinjau dari Segi Konteks Kebudayaan - Dewi Isma Aryani (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2014)
Pet Society offers a fantasy world of simulation through gameplay and environment as well as game characters. The design of each character is able to arouse its fans curiosity and addictive feeling to improve their pet character to the maximum level. This is a qualitative research conducted through the application of cultural theory that includes internal and external factors on character design and its visual transformation. Proximity analysis on character's visual elements and meaning, conducted to interpret the reflection of the game designer ideas as well as pet lover's ideology. The research shows that every pet character in this game is a form of representation of the player from the real world to the virtual world. Those pet's visual form diversity becomes the essence of player diversed character creation.